A new subfamily, genus, and species of Cephidae (Hymenoptera) from Australia - Smith, David R.; Schmidt, Stefan (Zootaxa, 2009)
Australcephinae, n. subf., is described from Queensland, Australia, based on Australcephus storeyi, n. gen., n. sp. This is the only cephid known from Australia and one of the few from the Southern Hemisphere. A key is given for the three recognized subfamilies of Cephidae.